Evaluation of the effect and residuality of Bacillus thuringiensis formulated in pills, in the control of Aedes aegypti (Dip: Culicidae) in Cali, (Colombia) - MORALES, CARLOS ANDRÉS; SUÁREZ, MARCO FIDEL (Revista Colombiana de Entomología, 2003)
In the search of control alternatives for Aedes aegypti the mosquito vector of dengue fever, a formulation in pills of Bacillus thuringiensis isreeliensis in containers to store water was evaluated. In Cali three zones were selected to intervene: urban zone Jarillón de Floraría (located on Cauca river is the border), rural zone Montebello and Brisas de Montebello. In these siles 101 deposits between tanks and metallic barriers were treated, taking 20 containers as a control group. The number of larvae in the containers was counted, with a ladle of approximately 500 cc. Before the application four samples by container were taken, a BTI pill for each 50 Lt of water was applied. Evaluations post-treatment were conducted at J 5, 30 and 40 days; with the obtained data the percentage of larvae reduction was found. After this, the pills were evaluated with community participation, a total of 49 containers among tanks and metallic barriers were used. taking 11 containers as a control group, the containers were marked each 50 Lt as an indication of pills amount needed. For each house were given pills for two treatments; post-treatment evaluations were conducted at 20, 40, 60, and 80 days, the method described in the first evaluation was used. The pupae reduction percentage obtained on the evaluation at 30 days was 100, 89, and 93% in Jarillón de Floralia, Brisas de Montebello y Montebello respectively, and 90, 76, and 4% at 45 days for the same localities. The percentage of reduction in pupas obtained on the evaluation with the community at 40 days was 99 and 100% in Brisas de Montebello and Montebello respectively, and 83 and 100% at 80 days for the same localities. This last value, obtained at 80 days, is not reflecting the pills residuality, which indicates that the community that participated in the intervention applied the second dose supplied since the start of the study. The BTI pills formulation is an effective tool Aedes aegypti control in water containers.